Analytically derived fixed termination time for stepwise inertial control of wind turbines—Part II: Application strategy. (October 2020) - Guo, Yichen; Bao, Weiyu; Ding, Lei; Liu, Zhifan; Kheshti, Mostafa; Wu, Qiuwei; Terzija, Vladimir
Highlights: The impact of the incremental power on the system frequency response is investigated. The analytical determination of the incremental power is proposed. The application strategy of the fixed termination time (FTT) for a wind farm is proposed. Abstract: By applying stepwise inertial control (SIC) on wind turbines (WTs), a secure system frequency response after large active power imbalances in the system can be achieved. In Part I of this paper (Ding et al., submitted for publication), a novel approach for determining when to terminate the SIC is presented. In this context, a new analytical expression for a fixed termination time (FTT) is derived. In order to optimally implement the FTT concept, both the parameters of the system frequency response (SFR) model and the incremental power during the SIC process must be known. This paper is providing answers to these questions and furthermore proposes an advanced application strategy for the FTT concept. The new strategy improves the frequency nadirs and prevents the WTs' rotor speed from violating the lower permissible limit during the SIC process. Using the least squares algorithm, the unknown SFR model parameters are estimated from the frequency measured at the point of common coupling (PCC) of the wind farm. The incremental active power is determined considering the effect of the incremental power on the frequency nadirs and the releasable kinetic energy of the WTs. The performance of the proposed new application strategy is verified using a modified IEEE 39-bus test system.